Political Ecology of Environmental Conflict in Wadas Village, Purworejo Regency - Sheha Putri; Eka Rahayu; Amanda Nazarina; Shanti Dewi; Sihidi, Iradhad Taqwa (Konsultan Surya Buana, 2026)
This study analyzes the agrarian and environmental conflict in Wadas Village, Purworejo Regency, which arose from the planned andesite mining to support the construction of the Bener Dam, a National Strategic Project. Using a political ecology perspective, this study examines how power relations between the state, elite interests, and local communities shape the development policy-making process. The research method used is a qualitative descriptive study based on documentation, utilizing data sources in the form of scientific articles, civil society organization reports, government policy documents, environmental impact analysis (EIA) documents, and media coverage. The results show that the mining plan has the potential to cause significant ecological degradation, particularly affecting the sustainability of water springs, soil stability, and the local community's agricultural system. In addition to the ecological impacts, this conflict also triggers socio-political degradation at the grassroots level, characterized by community polarization, weakened social solidarity, narrowed space for public participation, and the emergence of repressive actions by state officials. The research findings indicate a pattern of state capture in development policy, where state decisions reflect the economic-political interests of elites rather than the interests of affected communities. The green development narrative used by the government serves to legitimize the practice of natural resource extractivism. On the other hand, the resistance of the Wadas community demonstrates the residents' political capacity to defend their living space through collective mobilization and the utilization of local knowledge. This research confirms that the Wadas conflict is a question of ecological justice, citizenship rights, and democracy in development practices in Indonesia